Is the Digital Economy Partnership Agreement Effective in Export of Digitally Deliverable Services? The Case of Türkiye - TÜRKARSLAN, Mustafa Engin (Theoretical and Practical Research in Economic Fields, 2025)
This study examines the potential of the Digital Economy Partnership Agreement (DEPA) in addressing the challenges faced by Turkish businesses in e-commerce and e-export activities. It begins with a comprehensive analysis of the concepts of e-commerce and e-export, focusing on the digitalization of international trade. The study then evaluates the provisions of DEPA, particularly those relevant to the specific barriers encountered by Turkish e-commerce and e-export businesses. The findings suggest that DEPA includes various mechanisms that could help mitigate these challenges and enhance Türkiye’s integration into the digital economy. The research employs a panel data analysis using the Fixed Effects Model with Driscoll-Kraay (FE-DK) standard errors to assess the impact of DEPA on the export of digitally deliverable services alongside other key independent variables. Data from DEPA founding countries New Zealand, Singapore, Chile, and Türkiye, which is not a party to the agreement, are analyzed. The empirical results highlight the significance of a secure internet infrastructure and structured international agreements, such as DEPA, in fostering the growth of digital services exports. Moreover, participation appears to positively influence export performance, although the statistical significance varies depending on model specification.